Tuning the perpendicular magnetic anisotropy in Co/Pt multilayers grown by facing target sputtering and conventional sputtering. (15th January 2022) - Yıldırım, Oğuz; Marioni, Miguel A.; Falub, Claudiu V.; Rohrmann, Hartmut; Jaeger, Dominik; Rechsteiner, Marco; Schneider, Daniel; Hug, Hans J.
Graphical abstract: Abstract: Magnetic properties of [Co(0.4 nm)/Pt(0.7 nm)] 5 multilayers are tailored by controlling the sputtering voltage during growth of cobalt layers by a facing target cathode. It is shown that increasing sputtering voltage up to 150 V leads to an improved crystalline texture and this results in larger magnetic anisotropies together with increased out-of-plane coercive fields. At a higher cathode voltage of 540 V, however, crystalline texture quality slightly worsens and this is accompanied by a decrease in the effective anisotropy. Using facing target cathode sputtering, the crystalline structure of the multilayers can be controlled without applying any heat treatment and this can be utilized to optimize the magnetic properties of Co/Pt multilayers for specific applications.